2013
DOI: 10.1007/s00775-013-1047-8
|View full text |Cite
|
Sign up to set email alerts
|

Yeast copper–zinc superoxide dismutase can be activated in the absence of its copper chaperone

Abstract: Copper–zinc superoxide dismutase (Sod1) is an abundant intracellular enzyme that catalyzes the disproportionation of superoxide to give hydrogen peroxide and dioxygen. In most organisms, Sod1 acquires copper by a combination of two pathways, one dependent on the copper chaperone for Sod1 (CCS), and the other independent of CCS. Examples have been reported of two exceptions: Saccharomyces cerevisiae, in which Sod1 appeared to be fully dependent on CCS, and Caenorhabditis elegans, in which Sod1 was completely in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It is known that there is no correlation between the levels of SOD1-mRNA, apo-SOD1, holo-SOD1 and CCS-mRNA, as a CCS-independent pathway of copper delivery to SOD1 exists. 56 The content of Cox4i1-mRNA, as well as its protein product, decreased together (Fig. 8A-C).…”
Section: Expression Of Genes Associated With Copper Metabolismmentioning
confidence: 88%
“…It is known that there is no correlation between the levels of SOD1-mRNA, apo-SOD1, holo-SOD1 and CCS-mRNA, as a CCS-independent pathway of copper delivery to SOD1 exists. 56 The content of Cox4i1-mRNA, as well as its protein product, decreased together (Fig. 8A-C).…”
Section: Expression Of Genes Associated With Copper Metabolismmentioning
confidence: 88%
“… 296 Moreover, 30–50% of the disulfide bond of the yeast SOD1 was oxidized without CCS under these conditions. 296 …”
Section: Copper–zinc Superoxide Dismutasementioning
confidence: 96%
“…Although the activation of Saccharomyces cerevisiae SOD1 was originally believed to rely totally on CCS, with strict requirements for copper and O 2 , , it has recently been found that 15–20% of the yeast SOD1, when overexpressed in the absence of CCS, was able to acquire copper in vivo and to rescue the lysine auxotrophy, even in media depleted of copper . Moreover, 30–50% of the disulfide bond of the yeast SOD1 was oxidized without CCS under these conditions …”
Section: Copper–zinc Superoxide Dismutasementioning
confidence: 99%
“…It requires selective binding of copper and zinc ions, formation of the intrasubunit disulfide bond between Cys-57 and Cys-146, and dimerization of two subunits. The copper chaperone for Sod1 (CCS) 3 plays a critical role in copper insertion and disulfide oxidation in vivo (4,5), although a CCSindependent pathway has also been discovered (6,7). It is made even more complex by the fact that the entire maturation process takes place independently in its two principal intracellular locations.…”
mentioning
confidence: 99%